2022
DOI: 10.1038/s41522-022-00279-y
|View full text |Cite
|
Sign up to set email alerts
|

Citizen-science reveals changes in the oral microbiome in Spain through age and lifestyle factors

Abstract: The relevance of the human oral microbiome to our understanding of human health has grown in recent years as microbiome studies continue to develop. Given the links of the oral cavity with the digestive, respiratory and circulatory systems, the composition of the oral microbiome is relevant beyond just oral health, impacting systemic processes across the body. However, we still have a very limited understanding about intrinsic and extrinsic factors that shape the composition of the healthy oral microbiome. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…As a result of examining the effects of different patterns of smoking behaviors on oral health, the high-level maintenance pattern is found to be very vulnerable compared to that of the non-smoking pattern. This correspond well with previous studies that smokers are more likely to be exposed to oral diseases than non-smokers [ 4 , 25 ], and the studies that revealed smoking as one of the crucial factors influencing changes in the oral microbial ecosystem at the biological level [ 26 ]. It should be noted that there is no difference in the oral health between the decreasing pattern and the decreasing after increasing pattern compared to the non-smoking pattern.…”
Section: Discussionsupporting
confidence: 92%
“…As a result of examining the effects of different patterns of smoking behaviors on oral health, the high-level maintenance pattern is found to be very vulnerable compared to that of the non-smoking pattern. This correspond well with previous studies that smokers are more likely to be exposed to oral diseases than non-smokers [ 4 , 25 ], and the studies that revealed smoking as one of the crucial factors influencing changes in the oral microbial ecosystem at the biological level [ 26 ]. It should be noted that there is no difference in the oral health between the decreasing pattern and the decreasing after increasing pattern compared to the non-smoking pattern.…”
Section: Discussionsupporting
confidence: 92%
“…The microbial oral community shifts constantly throughout an individual’s life due to extrinsic and intrinsic factors [ 3 , 18 , 19 , 20 , 21 ]. The oral cavity is exposed to exogenous microorganisms mainly through diet, drinking, air, kissing, and lifestyle [ 18 ].…”
Section: Oral Microbiome—a Quick Overviewmentioning
confidence: 99%
“…The oral cavity is exposed to exogenous microorganisms mainly through diet, drinking, air, kissing, and lifestyle [ 18 ]. Changes in oral pH, depressed immune system, presence of chronic diseases, and intake of antibiotics also affect the composition of the oral microbiome [ 19 , 21 ]. Nonetheless, despite all these factors accounting for inter-individual variability, an oral core microbiome has been pinpointed [ 14 , 22 ], and it refers to the microbial taxa or the genomic and functional attributes associated with those taxa that are characteristic of the oral cavity under healthy conditions [ 23 , 24 ].…”
Section: Oral Microbiome—a Quick Overviewmentioning
confidence: 99%
“…Furthermore, adherence to a specific diet seems to promote the opportunistic pathogenesis of some microorganisms 6 . In this context, the oral tract microbiome is gaining attention as a new target of omics studies, as it can capture humans' dietary habits, immune responses, and environmental factors 7 . The oral cavity represents one of the richest substrates for microorganisms to grow and establish complex microbial communities 8 .…”
Section: Introductionmentioning
confidence: 99%